Uji Aktivitas Antioksidan Fraksi Etil Asetat Daun Asam Jawa (Tamarindus Indica L) Dengan Metode DPPH (1,1 Diphenyl-2-Picrylhydrazil) - Megawasti Megawasti; Sukmawati Sukmawati; Aminah Aminah (Rumah Sakit Ibnu Sina, Makassar, 2021)
Tamarind leaves are plants that contain flavonoids that act as antioxidants. In the extract of Tamarind Leaves (Tamarindus Indica L), there are active compounds in the form of flavonoids, tannins, and saponins. The content in tamarind leaves can provide benefits, especially for health. This study aims to determine the antioxidant activity of the ethyl acetate fraction of tamarind leaves. The sample was used in the form of ethyl acetate fraction from tamarind leaf extract where the antioxidant analysis method used is the DPPH (1.1 Diphenyl-2-Pikrylhydrazil) reduction method which functions as a free radical compound. The antioxidant activity of the ethyl acetate fraction of tamarind leaves (Tamarindus Indica L) was measured using a UV-Vis spectrophotometer at a wavelength of 516 nm with various concentrations of 20,30,40,50, and 60 ppm. The comparison used is quercetin. From the results of this study, it can be concluded that the ethyl acetate fraction of tamarind leaves (Tamarindus Indica L) has strong antioxidant activity with an IC50 value of 20.05 g/mL as the standard for strong antioxidant activity is in the range of 10-50 g/mL.